2006
DOI: 10.1242/jcs.02960
|View full text |Cite
|
Sign up to set email alerts
|

The chromodomain protein, Chromator, interacts with JIL-1 kinase and regulates the structure ofDrosophilapolytene chromosomes

Abstract: In this study we have generated two new hypomorphic Chro alleles and analyzed the consequences of reduced Chromator protein function on polytene chromosome structure. We show that in Chro 71 /Chro 612 mutants the polytene chromosome arms were coiled and compacted with a disruption and misalignment of band and interband regions and with numerous ectopic contacts connecting non-homologous regions. Furthermore, we demonstrate that Chromator co-localizes with the JIL-1 kinase at polytene interband regions and that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
76
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(83 citation statements)
references
References 31 publications
7
76
0
Order By: Relevance
“…Mutations affecting the JIL-1 kinase (Wang et al, 2001), subunits of the NURF chromatin-remodeling complex (iswi and nurf alleles) (Badenhorst et al, 2002;Badenhorst et al, 2005;Deuring et al, 2000) as well as other chromatin-associated proteins, such as SU(VAR)205 (also known as HP1), SU(VAR)3-7 (Spierer et al, 2005) and Chromator (also known as Chriz) (Eggert et al, 2004;Rath et al, 2006), each result in structural defects of chromatin. The distortions are most clearly seen in the structure of male X chromosomes, resulting in the appearance of a puffed-X morphology, also referred to as 'bloated male X' or 'pompon' phenotype (Zhimulev, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Mutations affecting the JIL-1 kinase (Wang et al, 2001), subunits of the NURF chromatin-remodeling complex (iswi and nurf alleles) (Badenhorst et al, 2002;Badenhorst et al, 2005;Deuring et al, 2000) as well as other chromatin-associated proteins, such as SU(VAR)205 (also known as HP1), SU(VAR)3-7 (Spierer et al, 2005) and Chromator (also known as Chriz) (Eggert et al, 2004;Rath et al, 2006), each result in structural defects of chromatin. The distortions are most clearly seen in the structure of male X chromosomes, resulting in the appearance of a puffed-X morphology, also referred to as 'bloated male X' or 'pompon' phenotype (Zhimulev, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…We observed prominent binding of Chriz, Z4 (data not shown) and Jil-1, proteins that are typically found in decondensed chromatin as reported previously (Eggert et al, 2004;Gortchakov et al, 2005;Wang et al, 2001). Chriz and Jil-1 physically interact (Rath et al, 2006), and on Chriz knockdown both Jil-1 chromosomal binding and H3S10 phosphorylation are dramatically reduced, indicating that Chriz is required for chromosomal targeting of Jil-1 (Gan et al, 2011). Forced local recruitment of active Jil-1 kinase results in local chromatin decondensation (Deng et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Forced local recruitment of active Jil-1 kinase results in local chromatin decondensation (Deng et al, 2008). Hypomorphic mutations in Jil-1 and Chriz, by contrast, result in chromosome condensation and loss of interphase chromatin structure (Wang et al, 2001;Rath et al, 2006, Gan et al, 2011, similar to what is observed on loss of Z4 protein (Eggert et al, 2004). Besides these factors, we observed binding of the insulator proteins CP190 (Whitfield et al, 1988;Pai et al, 2004) and BEAF 32 (Zhao et al, 1995; data not shown) to the ectopic 61C7-8 position, resembling the situation at the endogenous site.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental evidence indicates that Mod (mdg4) is involved in meiosis I and chromosome segregation in males (Soltani-Bejnood et al 2007), in the regulation of chromatin assembly or disassembly (Gerasimova et al 1995), oogenesis (Buchner et al 2000), and germ-cell migration (Read et al 2000). JIL-1 has histone kinase activity (Jin et al 1999;Rath et al 2006;Zhang et al 2006) and is involved in the negative regulation of chromatin silencing and in chromosome organization. Deficiency of JIL-1 leads to strong enhancer of variegation (white-eye phenotype), counteracting even the suppressor-of-variegation effect of HP1 and Su(var)3-9 (Wang et al 2011).…”
mentioning
confidence: 99%